1994
DOI: 10.1139/v94-055
|View full text |Cite
|
Sign up to set email alerts
|

Application of electrogenerated triphenylmethyl anion as a base for alkylation of arylacetic esters and arylacetonitriles and isomerization of allylbenzenes

Abstract: Phenylacetic esters and phenylacetonitriles were alkylated with alkyl halides, at the position α to an ester or nitrile, either at room temperature (20 °C) or at −78 °C, by making use of electrogenerated triphenylmethyl anion (trityl anion). Double-bond isomerization of allylbenzenes was also effectively accomplished by use of this electrogenerated base (EGB).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…In an interesting electrochemical isomerization procedure, Nakajima and co-workers demonstrated that the triphenylmethyl anion, generated by way of a one-electron reduction under electrolysis, was able to isomerize a number of topical arylallyl compounds 1 . β-Methylstyrenes 2 were successfully obtained including those derived from safrole 6 , estragole 7 , allylbenzene 3 , and 1-allyl-3,4-dimethoxybenzene 17 (Scheme gives the generalized summary).…”
Section: Miscellaneous Methods For Isomerizing Allylbenzenesmentioning
confidence: 99%
“…In an interesting electrochemical isomerization procedure, Nakajima and co-workers demonstrated that the triphenylmethyl anion, generated by way of a one-electron reduction under electrolysis, was able to isomerize a number of topical arylallyl compounds 1 . β-Methylstyrenes 2 were successfully obtained including those derived from safrole 6 , estragole 7 , allylbenzene 3 , and 1-allyl-3,4-dimethoxybenzene 17 (Scheme gives the generalized summary).…”
Section: Miscellaneous Methods For Isomerizing Allylbenzenesmentioning
confidence: 99%
“…Tripodal 3 also exhibited an unexpected stoichiometry of 1:2 (3:In 3+ ). This can be explained by "allosteric coextraction", because while 3 provides only three acetic acid groups for neutralization of the In 3+ charge, it also provides a very active triphenylmethyl proton for the second In 3+ , which acts as carbon acid and has an estimated pK a value of 30 [55][56][57]. While very weak, the acid has sufficient strength to form a metal complex [58].…”
Section: %𝐿mentioning
confidence: 99%
“…[20] The electrogenerated triphenylmethyl anion acted as a base to isomerize allylaromatics. [21] Isomerization of allyl sulfides has been reported with NaOH or NaOEt, [22a, b] Pd(PCy 3 ) 2 (PCy 3 ¼ tricyclohexylphosphine), [22c] or tris(2,4-pentanedionate)ruthenium.…”
Section: Introductionmentioning
confidence: 99%